Genetic Variability and Character Interrelationship among Indigenous Germplasm of Turmeric (Curcuma longa). Issue 2 (2nd April 2016) - Gupta, A. K.; Mishra, Ritu; Lal, R. K.
ABSTRACT: Genetic study of turmeric ( Curcuma longa ) germplasm revealed natural and genetic variability for 13 agromorphological traits. High heritability (h2BS%) and high genetic advance (GA) along with high genotypic coefficient of variability (GCV) were recorded for rhizome dry and fresh weight, indicating that selection for these may provide good advance, as these were governed by additive gene effects. High co-heritability among the 13 agromorphological traits forms a good selection criterion for economic traits. Leaf length and thickness of stipulated tuber showed positive correlation with rhizome dry weight. Path coefficient study revealed that the highest direct contribution to rhizome dry weight was made by its fresh weight.